Amerila (Lepidoptera: Erebidae: Arctiinae) of Cameroon with morphological remarks on male and female genitalia - Przybyłowicz, Łukasz; Maicher, Vincent; László, Gyula M.; Sáfián, Szabolcs; Tropek, Robert (Zootaxa, 2019)
Amerila is one of the most studied Afrotropical genera of Arctiinae. However, based on a regionally constrained sample of specimens from Mount Cameroon, we show how superficial our knowledge on these tiger moths is. Among six collected Amerila species, A. femina’s female is described here for the first time, and A. mulleri and A. roseomarginata had never been recorded before in the country. Moreover, novel biological data are presented, including individual species’ elevational ranges. Finally, female reproductive organs of the genus are illustrated here for the first time. The value of such regional studies is highlighted, with some remarks on necessary requirements of such small-scaled field sampling.